2019 IEEE Power &Amp; Energy Society General Meeting (PESGM) 2019
DOI: 10.1109/pesgm40551.2019.8973724
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven Identification and Prediction of Power System Dynamics Using Linear Operators

Abstract: In this paper, we propose linear operator theoretic framework involving Koopman operator for the data-driven identification of power system dynamics. We explicitly account for noise in the time series measurement data and propose robust approach for data-driven approximation of Koopman operator for the identification of nonlinear power system dynamics. The identified model is used for the prediction of state trajectories in the power system. The application of the framework is illustrated using an IEEE nine bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…As pointed out in section I, majority of the data-driven approaches consider the availability of time-series information for all (or most) state variables (x(t)). Existing work on datadriven nonlinear dynamic characterization [24]- [33], either assumes that measurements for these states are available (as they can be generated in simulation studies); or else, a simple swing equation based 2 nd order dynamics are considered with δ i , ω i states and thus ignoring other higher order dynamics of system components.…”
Section: Need For Output Measurements Based Power Systems Dynamics Ch...mentioning
confidence: 99%
See 2 more Smart Citations
“…As pointed out in section I, majority of the data-driven approaches consider the availability of time-series information for all (or most) state variables (x(t)). Existing work on datadriven nonlinear dynamic characterization [24]- [33], either assumes that measurements for these states are available (as they can be generated in simulation studies); or else, a simple swing equation based 2 nd order dynamics are considered with δ i , ω i states and thus ignoring other higher order dynamics of system components.…”
Section: Need For Output Measurements Based Power Systems Dynamics Ch...mentioning
confidence: 99%
“…In particular, the Koopman operator provides a linear representation (not the linear approximation) for a nonlinear dynamical system. Recent work has shown that the linear operator based approach is suitable for stability studies [24], generator coherency identification [30], system inertia estimation [31], and PSS parameter tuning and controller design [32] and trajectory prediction [33]. One of the key assumptions in these works [24]- [33] is the availability of state measurements, i.e., it is assumed that time-series measurements are available for all dynamic states of a given system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Power systems data analysis is the current frontier of innovation, exploration and productivity, and its research is on the rise. Such data analysis has addressed diverse system areas like coherency groups identification [7], trajectory prediction to identify system dynamics from a noisy measurements [8], short-horizon wind power forecasting [9], online prediction of transient stability with renewables [10], photo-voltaic power production nowcasting in microgrids [11], power system collapse prediction [12], wide area control [13], load frequency control [14], and for renewable integration impact assessment [15].…”
Section: Introductionmentioning
confidence: 99%
“…This lifting can be approximated using data generated from the underlying nonlinear dynamics by the well-known Extended Dynamic Mode Decomposition (EDMD) algorithm [6]. These tools have been successfully applied in many domains such as fluid dynamics [7] and power systems [8,9], to understand the principle components/modes of given nonlinear dynamics [10]. Recently, Koopman theory has been introduced to the control synthesis tasks, in the hopes that a controller designed in the lifted space could be easier than that in the original state space.…”
Section: Introductionmentioning
confidence: 99%